A second reckoning : race, injustice, and the last hanging in Annapolis - Seligman, Scott D. (Potomac Books, an imprint of the University of Nebraska Press, 2021)
A Second Reckoning tells the story of the 1917 murder that led to the last hanging in Annapolis, Maryland, and makes an appeal for posthumous justice, especially where racial prejudice may have tainted a case.
Keywords: Snowden, John, -- 1890-1919 -- Trials, litigation, etc.; Trials (Murder) -- Maryland -- Baltimore County -- 20th century.; Hanging -- Maryland -- Baltimore County -- 20th century.; Discrimination in criminal justice administration -- United States -- History.; African Americans -- Civil rights -- History.; Pardon -- United States.; Evidence, Circumstantial -- United States.; United States -- Race relations -- History.; Discrimination dans l'administration de la justice pénale -- États-Unis -- Histoire.; Noirs américains -- Droits -- Histoire.; Preuve circonstancielle -- États-Unis.; États-Unis -- Relations raciales -- Histoire.; Procès (Meurtre) -- Maryland -- Baltimore (Comté) -- 20e siècle.; Pendaison -- Maryland -- Baltimore (Comté) -- 20e siècle.; African Americans -- Civil rights; Discrimination in criminal justice administration; Evidence, Circumstantial; Hanging; Pardon; Race relations; Trials (Murder); Maryland -- Baltimore County; United States; 1900-1999; History; Trials, litigation, etc.